2020
DOI: 10.1002/pld3.201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes involved in male sterility in wheat (Triticum aestivum L.) which could be used in a genic hybrid breeding system

Abstract: Wheat is grown on more land than any other crop in the world. Current estimates suggest that yields will have to increase sixty percent by 2050 to meet the demand of an ever‐increasing human population; however, recent wheat yield gains have lagged behind other major crops such as rice and maize. One of the reasons suggested for the lag in yield potential is the lack of a robust hybrid system to harness the potential yield gains associated with heterosis, also known as hybrid vigor. Here, we set out to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Stacking guides also can dramatically help increase the overall levels of mutations and mitigate the differences between mutation rates per guide. Single guide efficiencies can be large, ranging from 0 to 90%, in this work and previous studies targeting homoeologs genes 7 to 45% of plants were edited at a particular locus (Milner et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Stacking guides also can dramatically help increase the overall levels of mutations and mitigate the differences between mutation rates per guide. Single guide efficiencies can be large, ranging from 0 to 90%, in this work and previous studies targeting homoeologs genes 7 to 45% of plants were edited at a particular locus (Milner et al, 2020).…”
Section: Discussionsupporting
confidence: 58%
“…Wheat has a relatively low rate of CRISPR/Cas9 editing and it is thought that most are induced during the first few days after transformation. In general, an efficiency of about 10% overall mutation rate is to be expected (Howells et al, 2018;Liu et al, 2019;Zhang et al, 2019;Milner et al, 2020). Recently, we have shown that stacking guides can improve efficiency greatly and help create full knockouts of close to 10% in wheat (Milner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that this regulation is linked with the maintenance of sugar content in photosynthesising tissue pre‐ and post‐anthesis, which in turn decelerates the decline in net carbon balance to achieve heat tolerance (Julius et al, 2017; Zhou et al, 2017). Concurrently, SWEET, for example, RPG1 (Milner et al, 2020), and SUC/SUT, for example, SUC1 (Sivitz, Reinders, & Ward, 2008; Xu, Chen, Yunjuan, Chen, & Liesche, 2018), sugar transporters have been implicated in pollen development, most significantly by facilitating water transport out of endothecium cell walls to increase tension and enable pollen dehiscence (Keijzer, 1987; Wilson et al, 2011). Consequently, photosynthetic activity in reproductive structures, especially anthers (Clément & Pacini, 2001), may result in fine‐tuning of sugar transporter activity given elevated temperatures in order to maintain cellular sugar status.…”
Section: The Capacity Of Non‐foliar Photosynthesis To Contribute To Yield and Reproductive Development During Heat Stressmentioning
confidence: 99%
“…Similarly, it has been observed that for TaNP1 , the wheat homolog of the rice OsNP1 and maize ZmIPE1 genes encoding a putative glucose-methanol-choline oxidoreductase, knockouts in all three homeologs are required for male sterility [ 34 ]. Milner et al [ 36 ] identified two male fertility genes in wheat, CALS5 - and RPG1-like , through gene expression analysis. Functional analysis of these genes through CRISPR/Cas showed that knockouts in all three homeologs are required to obtain male sterile plants [ 36 ].…”
Section: Sporophytic Genes Involved In Anther and Pollen Development In Wheatmentioning
confidence: 99%